An evaluation of luxury consumers’ pre-purchase information search and shopping preference between physical and online stores: a Singapore study - Chen, Sabrina Hui Ping (2021)
The e-retail landscape has opened endless possibilities of virtual opportunities. Luxury brands have traditionally used physical stores to sell their luxury products but in a modernised world, e-commerce has demanded change in the commercial landscape. As consumers are the main drivers in the retail industry, luxury companies focus marketing strategies towards them. This study investigates the consumer’s pre-purchase information gathering and purchasing behaviours across online and physical stores for small luxury leather products such as wallets, handbags and belts in Singapore. With the findings, the author aims to identify how demographics impact online and offline channel shopping preferences to develop recommendations improving online and physical stores in accordance to consumer’s shopping expectations and preferences.